A ATERRA – Associação dos Trabalhadores Rurais da Reforma Agrária: Desafios, obstáculos e contradições na construção e organização de uma alternativa de Economia Solidária - Rocha Filho, Alnary Nunes (2010)
This research deals the general topic of the solidary economy, aiming an approach to the solidary attempts related process that are encouraged by public policies of developmental and/or social character. Through it discusses the subject as it comes array of alternatives for local and regional development. The study also brings the historical process of building the solidary economy, in many situations in which their ideology was present and also the ways in which the speech was appropriate for workers, in their struggles and achievements. The study aimed to explore the process of socio-territorial activities of the ATERRA - Associação dos Trabalhadores Rurais da Reforma Agrária, in the pre-settlement Emiliano Zapata, located in the District of Itaiacoca, the city of Ponta Grossa, Pr. Observing thus, the possible creation of new work relations, through the solidary economy, and has the intention to also create new habits of life. The research was primarily done through observation and provision of advisory services relating to attempts to overcome the legal obstacles, tax, fiscal and current structural conditions of existence of pre-settlement. Through the work of the Extension Program, IESol – Incubadora de Empreendimentos Solidários, to relate to UEPG - Universidade Estadual de Ponta Grossa, this study aims to reflect on the processes of organizing of ATERRA and his associates, which in some way, are is not of decent social and economic standing. The participation of members, tries to make the self management and solidarity cooperation, strategies for struggle and resistance, as the ideals of the MST – Movimento dos Trabalhadores Rurais Sem Terra. The subjects involved in this research, appear in public and academic debates on citizenship and democracy and seeking to discuss how public policies that seek to overcome our social and regional inequalities, confronting the processes that maintain these crystallized inequalities in Brazilian society.